Pendidikan dan Perubahan Sosial - Wardani Sihaloho; Dini Rosmana Tanjung; Septi Ayu Harahap; Adawiyah Barus; Swandari Purnama Ningsih; Alia Rohali (Jurnal Dirosah Islamiyah, 2023)
This research can provide better insight into how education can help people overcome various social and economic problems, as well as how education can adapt to the social changes taking place in Indonesia. Thus, this research can make a significant contribution in improving the quality of education in Indonesia and helping people achieve better social and economic progress. The purpose of writing this article is to know and understand how important the role of education is in facing and preparing for the social changes that happen. with literature study data collection techniques, such as scientific papers, journals, and so on. Literature study is by understanding and examining various scientific papers that are relevant and related to the focus of the discussion. From various sources obtained and studied, resulted in an understanding that education is a very important thing in life. The important role of education in life and in social change is to equip and prepare us to be better and to face or overcome various problems that occur as a result of social change. Key words: role, social change, culture, education